“Efectos del dimenhidrinayo aplicado por via endovenosa en la fase activa de labor de parto. Hospital de apoyo de Chachapoyas, Periodo marzo de 1996 a Marzo de 1997” - Ramírez Rodas, Segundo Benedicto (1997)
Currently delivery normal or eutocico, should be diri & gone through modern techniques and with the use of drugs appropriate to ensuring that their duration is the minimum possible, with lower risk and maximum pain attenuation; all benefit. the binomial Muki German and into a really physiological process. The force uterine normal can calculate is with a system of catheter intrauterine (transducer) _ of that way the tone of resting basal normal, is less to 5 Torr to the beginning of the phase of latency and increases of 10 to 12 Torr in the phase active (1). Labour increases the strength and frequency of uterine contractions; allowing a progression fast until the expulsion of the fetus. Advancing cervical dilation during childbirth; It reduces total uterine activity spent by every cm. forward. So, it is necessary to take this increase in efficiency of uterine labor to assess factors such as drugs and its effects on the progress of the work...